The effect of inflation and interest rates on the stock price of Pt Bank Negara Indonesia tbk 2015-2024 - Yulia Prismawati; Rizka Wahyuni Amelia (Indonesia Accounting Research Journal, 2025)
This study aims to determine the effect of inflation, interest rates on stock prices at PT. Bank Negara Indonesia Tbk for the period 2015-2024. The research method used is quantitative. Data analysis Heteroscedasticity, Autocorrelation, Multiple Linear Regression, t-test, F-test, Correlation Coefficient and Determination Coefficient. The results of the t-test show a comparison that Inflation t-count 2.943> 2.447, it can be concluded that there is an effect of inflation on stock prices. For Interest Rates t-count -2.936 4.74 it can be concluded that simultaneously there is an influence of inflation, interest rates and stock prices of PT. Bank Negara Indonesia Tbk.